UMKM Mocaf Desa Padi sebagai Pilar Ketahanan Pangan Nasional: Implikasi Hukum Tata Negara Terhadap Kedudukan dan Peran Sektor Internal - Derta Nur Anita; Ni Kadek Intan Rospita Yanti; Nanda Putri Aminati; Fatimah Azzahra; Ade Liya Retno Wulandari; Azzahra Airizka Ukhwahap; Imelda Yunita Puspitasari; Inova Tanzillal Al-Rizki; Devinta Rahmayanti; Fareza Radita Pasyah; Chahyo Nugroho; Reggy Risky Darmawan; Aida Nurfitria; Firnanda Fatimatuz Zahroh; Tia Aulia Irfan; Devi Afifah Pusparina; Puput Setyo Rahayu; Muhammad Bakhrudin Zaki; Haydir At Bilal; Redhita Virga Agustin; Rendi Dwi Amirudin; Alan Emillul Fata; Edo Dio Pradana; Muhammad Syarif Fudin; Prayoga Putra Meygianto; Diaz Rahmat Kusumaatmaja (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
The high dependence of national food on imported commodities, especially wheat, creates vulnerabilities in the aspect of National Food Security. This study examines the position and role of Modified Cassava Flour (Mocaf) Micro, Small, and Medium Enterprises (MSMEs) in Padi Village as a pillar of local food diversification and its implications from the perspective of Constitutional Law (HTN) on the internal sector (community, MSMEs, and Village Government). Mocaf, as a gluten-free cassava derivative product, has the potential to be a substitute for wheat flour. The research method used is Empirical Normative Law with a conceptual and legislative approach, reinforced by primary data regarding the operational model of MSMEs in Padi Village. The results of the study indicate that Mocaf MSMEs at the village level act as strategic legal subjects in realizing Article 33 paragraph (3) of the 1945 Constitution (UUD 1945) and Law Number 18 of 2012 concerning Food. The implications of HTN are seen in the need for regulatory harmonization and strengthening village autonomy through budget policies and assistance that ensure the sustainability of production and marketing. The position of MSMEs demands stronger recognition of the internal role of villages in the national food governance structure.